A study of the galactic star cluster NGC 2547 - Fernie, John Donald (Department of Astronomy, 2020)
The following thesis has been undertaken primarily as an observational study. Accordingly, theoretical discussion and speculations have been kept to a minimum, formulas in most case being early quoted and references given for their derivations. Since the observational techniques used are nearly all in standard practice, they have not been fully described, while descriptions of their reductions have been relegated to appendices.